Exploring Students’ LOTS and HOTS in Answering Reading Questions - Armala, Intan; Fauziati, Endang; Asib, Abdul (Journal of Education Technology, 2022)
In the twenty-first century, the education world must fulfill the demands for teaching and learning connected to thinking abilities. For people who are more nuanced and intellectual, the ability to think is necessary. Students must be able to think to reach their learning objectives. Teachers face dilemmas in the classroom in terms of higher-order thinking skills. Teachers incorporate higher-order thinking skills into the teaching and learning process to provide experiences to students, especially in answering questions about higher-order thinking skills. Students often have difficulty answering HOTS questions. As a result, students have difficulty answering reading comprehension questions. This study aimed to explore what students' LOTS and HOTS were in response to reading questions. This type of research is descriptive and qualitative. Data was collected by giving a reading test to 18 students. The instrument used in collecting data is a questionnaire. The data analysis technique is descriptive qualitative analysis. The results showed that the student's ability to answer reading questions based on the LOTS was good. Second, the ability of students to answer reading questions based on HOTS is lacking. Third, the difference in student's ability to answer reading questions based on LOT and HOT is enough. As a result of these findings, students' ability to answer reading questions based on LOTS and HOTS should be improved.